Introduction of a prescribing ward round to reduce prescribing errors on a paediatric intensive care unit. Issue 4 (3rd July 2020) - Walsh, Aisling; Booth, Rachelle; Rajani, Kalindi; Cochrane, Lynne; Peters, Mark; du Pré, Pascale
Abstract : Our paediatric intensive care unit (PICU) performs active surveillance for prescribing errors and detects a mean of 1.66 with an SD of 0.18 total prescription errors per occupied bed day. The primary aim of this project was to reduce the number of prescribing errors in PICU. The secondary aims were to improve the workflow in the unit and reduce the time staff spent on medication queries/prescribing. We introduced a daily multidisciplinary prescribing round to our PICU. Prescribing errors reduced, with the mean number of total prescription errors per bed day falling from 1.66 (0.18) to 1.19 (0.13), the mean number of clinical prescription errors per bed day falling from 0.46 (0.09) to 0.3 (0.07), and the mean number of non-clinical prescribing errors per bed day falling from 1.12 (0.15) to 0.67 (0.1). Forty-eight staff responded to the survey, 39 of whom had been directly involved in the rounds. The majority (37 of 39; 95%) said the prescribing round reduced the overall time they spent on prescribing/medication queries during their shift, and 9 of 10 (90%) prescribers said that they were interrupted fewer times for medication queries while doing other tasks. Almost all (47 of 48; 98%) said that they thought the prescribing ward round should continue. Introduction of a prescribing round with senior medical and pharmacist involvement was associated with a reduction in prescribing errors as well as reduction in the overall time staff spent on medication queries and prescribing. The round was well received by staff, with 98% wanting it to continue.